Teacher's Perceptions of Bullying in a Rural School District - Jackson, Rutha Mae (2018)
Bullying is a serious problem that can interfere with children's developmental and learning processes but can be difficult to manage and diffuse. The purpose of this qualitative case study was to examine teachers' perceptions and experiences with managing student bullying in a middle school in central Georgia. Olweus's effective classroom management model served as the conceptual framework to guide this study. The research questions focused on teachers' perceptions of their current practices of diffusing bullying situations and their experiences with bullying occurrences. A case study design was used to capture the insights of 10 middle school teachers through interviews, and purposeful sampling was used to select the participants. The participants were middle school teachers with 1 or more years of teaching experience who have experienced student bullying. Emergent themes were identified through an open coding process, and the findings were developed and checked for trustworthiness through member checking, rich descriptions, and researcher reflexivity. The findings revealed that teachers manage student bulling in independent ways based on their own experiences, that teachers should identify and share a unified definition of bullying, and that teachers would benefit from professional development to help them better manage student behavior consistently within the school. This study may influence positive social change by providing teachers and administrators with crucial information needed to implement an organized, systematic approach to reduce student bullying occurrences and to provide students with a safe learning environment